Powders and grains 2005. proceedings of the 5th International Conference on Micromechanics of Granular Media, Stuttgart, Germany, 18-22 July, 2005 /: proceedings of the 5th International Conference on Micromechanics of Granular Media, Stuttgart, Germany, 18-22 July, 2005. Volume 1 : (2005) - Unknown
No abstract available